IT’S THE PROPERTY, STUPID! BUT HOW CAN WE GET RID OF IT? - Ferreira, Alvaro (Geo UERJ, 2024)
The purpose of our research is to identify paths that lead us beyond property. It’s important to us to do more than criticize private property; it’s also necessary to think beyond public property. We would like to reach something that goes beyond both. We aren’t referring either to the private property of capitalism or to the public property of socialism; we refer to the idea of the common in communism. The understanding of the common requires that we envision a society different from capitalist society. The common isn’t a third option to the private and the public (and is not equivalent to the latter) but a path antagonistic to capital and its means of production. It’s necessary to keep in mind that the ‘realization’ of the common through state property constitutes the very destruction of the common by the state. The notion of property, in and of itself, excludes the common, not only in terms of the use of goods, but also in the realm of production, given that it ratifies a division between owners and non-owners. The defense of the common carries with it the denial of property, public or private and also of the State. It’s a process. This perspective is of real importance, because the institution of private property and the State itself – which feed each other – is the basis for the support of capitalism.